Development of IoT-Based Teaching Aids to Enhance Students’ Conceptual Understanding of Global Warming - Grace Purba; Dedy Hamdani; Bodi Gunawan (FKIP - Universitas Riau, 2026)
This study aims to develop and evaluate the feasibility and effectiveness of Internet of Things (IoT)-based teaching aids in improving students’ conceptual understanding of global warming. The study is motivated by the limited use of interactive learning media and the dominance of teacher-centered instruction, which contribute to low conceptual understanding among students. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 30 tenth-grade students from a public high school in Bengkulu City. The instruments used included a needs analysis questionnaire, expert validation sheets, a conceptual understanding test administered as a pretest and posttest, and a student response questionnaire. The results show that the developed IoT-based teaching aids achieved a very high feasibility level, with an average validation score of 98.77%. Students’ conceptual understanding improved significantly, as indicated by the increase in average scores from 34.58 (pretest) to 86.25 (posttest), with an N-Gain value of 0.78, categorized as high. Student responses were also rated as excellent, indicating positive engagement and active participation during the learning process. Therefore, the IoT-based teaching aids are considered both feasible and effective in supporting more contextual, interactive, and meaningful learning experiences in physics education.